Determining the optimal lysine:calorie ratio for growth performance of PIC nursery pigs - J D Schneider; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Two studies were conducted to evaluate the effects of increasing dietary lysine and energy density on nursery pig performance. Experiment 1 was organized as a combination of two simultaneous experiments,with one set of diets consisting of five treatments with increasing true ileal digestible (TID) lysine (1.11, 1.19, 1.26, 1.34, and 1.42%) and the second set of diets consisting of five treatments with increasing energy density (1,341, 1,408, 1,475, 1,542, and 1,609 kcal/lb). The highest level of both lysine and energy density (1.42% and 1,609 kcal/lb, respectively) were combined as one diet and used in both the lysine and energy-density titrations, to give a total of 9 diets for the 10 treatments. Pigs (PIC, avg BW = 22.5 lbs) were randomly allotted to eight replications with five pigs per pen, on the basis of BW. Overall (d 0 to 21) in Experiment 1, increasing TID lysine linearly increased (P<0.01) ADG and improved (linear, P<0.01) feed efficiency. Increasing energy density had no effect on ADG, but it decreased (linear, P<0.01) ADFI, which resulted in a linear (P<0.01) improvement in F/G. Regression analysis of the response surface was used to predict the optimal lysine: calorie ratios for ADG and F/G of 4.06 and 3.92 g lysine/Mcal ME for the PIC pigs used in this experiment. In Experiment 2, pigs (PIC, avg BW = 16.6 lbs) were fed diets with two different energy densities (1.34 or 1.49 Mcal ME/lb) with TID lysine:calorie ratios ranging from approximately 3.5 to 4.5 g/Mcal ME. There was an energy density × TID lysine:calorie ratio interaction observed for F/G. Pigs fed the low-energy diets had the greatest ADG, at a lysine: calorie ratio of 4.55. For pigs fed the high-energy diets, ADG improved as the lysine:calorie ratio improved to 4.26 g of TID lysine/Mcal ME. There was a quadratic (P<0.03) improvement in feed efficiency as the lysine:calorie ratios were increased for the pigs fed the low-energy diet, with the best F/G value observed at 4.55, but the pigs fed the high-energy diets experienced a linear (P<0.01) improvement in F/G as the lysine:calorie ratios were increased. These results suggest that the optimal lysine-to-calorie ratio is 4.26 to 4.55 g of TID lysine/Mcal ME for 20- to 50-lb PIC pigs in these facilities.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Lysine; Energy; Nursery pig